2021
DOI: 10.3389/fnagi.2021.790626
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Attenuated Inversion Recovery Vascular Hyperintensity in Cerebrovascular Disease: A Review for Radiologists and Clinicians

Abstract: Neuroradiological methods play important roles in neurology, especially in cerebrovascular diseases. Fluid-attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH) is frequently encountered in patients with acute ischemic stroke and significant intracranial arterial stenosis or occlusion. The mechanisms underlying this phenomenon and the clinical implications of FVH have been a matter of debate. FVH is associated with large-vessel occlusion or severe stenosis, as well as impaired hemodynamics. Possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…In comparison, in the majority of studies that demonstrated an association between FVH and unfavorable outcomes, the symptom-to-imaging time was 12–24 h or longer [ 36 38 ]. Our findings confirmed that FVH was independently associated with poor prognosis, which we believe is related to the fact that the patients we enrolled who did not receive timely vessel recanalization and underwent MR scanning within 72 h. Previous studies believed that FVH may serve as an imaging marker of leptomeningeal collaterals within 6 h of symptom onset or within the time window of reperfusion treatment [ 39 ]. The extent of FVH may indicate the amount of brain tissue vulnerable to ischemia, which can be reversed with reperfusion therapy to reduce the size of the eventual lesion and improve functional outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…In comparison, in the majority of studies that demonstrated an association between FVH and unfavorable outcomes, the symptom-to-imaging time was 12–24 h or longer [ 36 38 ]. Our findings confirmed that FVH was independently associated with poor prognosis, which we believe is related to the fact that the patients we enrolled who did not receive timely vessel recanalization and underwent MR scanning within 72 h. Previous studies believed that FVH may serve as an imaging marker of leptomeningeal collaterals within 6 h of symptom onset or within the time window of reperfusion treatment [ 39 ]. The extent of FVH may indicate the amount of brain tissue vulnerable to ischemia, which can be reversed with reperfusion therapy to reduce the size of the eventual lesion and improve functional outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…1 Third, MR images were mainly obtained within 4 hours of stroke onset, and results might differ at later time points when information on collaterals might be more useful for treatment decisions. 10,11 Fourth, some patients were excluded because of FLAIR artifacts; however, this exclusion concerned ,2% of the total sample. Fifth, although ratings of FVH ASPECTS and FVH-DWI mismatch ASPECTS remain subjective, interobserver agreement was good.…”
Section: Discussionmentioning
confidence: 99%
“…Although FVH have been proposed as a surrogate marker of collateral status, 9 the relation between FVH and collateral status remains incompletely understood. 10,11 Actually, FVH may not only represent retrograde collateral flow but also reflect slow anterograde flow or even stationary blood.…”
mentioning
confidence: 99%
“… 9 Fluid-attenuated inversion recovery (FLAIR) vascular hyperintensities (FVHs) are serpentine or linear hyperintensities that are best visualized within the Sylvian fissure ipsilateral to acute ischemic stroke. 10 , 11 FVH has demonstrated good diagnostic performance for the identification of LASO in stroke, but the relationship between FVH and TIA is still undetermined. The purpose of this study was to investigate the prevalence of FVH and the clinical–radiological correlation in patients with TIA.…”
Section: Introductionmentioning
confidence: 99%